Concentration of suspension and temperature as factors of pathogenicity of entomopathogenic nematodes for the control of granary weevil, Sitophilus granarius (L.) (Coleoptera: Curculionidae) - Stanislav TRDAN; Nevenka VALIČ; Gregor UREK; Lea MILEVOJ (Acta Agriculturae Slovenica, 2005)
Efficacy of four species of entomopathogenic nematodes (Steinernema feltiae, S. carpocapsae, Heterorhabditis bacteriophora, H. megidis) for the control of granary weevil adults (Sitophilus granarius) was tested under laboratory condition. Suspensions of nematodes were applied in three concentrations (5.000, 10.000, and 20.000 IJs per ml) at three temperatures (15oC, 20oC and 25oC). After one week mortality of the beetles was assessed. No significant differences in the percentage of mortality were determined between treatments with S. feltiae, S. carpocapsae and H. bacteriophora, while H. megidis was the least efficient. Mortality of the beetles was statistically significantly higher at 20 and 25 oC. Influence of the concentration of the nematode suspension was proved to be less important in biological activity of biological agents in question.